PENGEMBANGAN MODUL BUDAYA LITERASI: STRATEGI MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MAHASISWA DALAM PENGGUNAAN MEDIA SOSIAL - Mawar Saron, Geba; Windrawanto, Yustinus; Maria Agustin, Adhi Krisna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Critical thinking is a very important skill to deal with the complexity of information, especially in the digital era that we are currently living in. Media literacy has a very vital role in developing critical thinking skills, because it helps individuals to sort, analyze, and evaluate information objectively. Currently, we often witness the rise of hoax news, provocative content, and many students who have difficulty in analyzing problems because the convenience offered by the digital era often makes them complacent. This study aims to investigate the relationship between media literacy and critical thinking skills, and to identify strategies that can be applied to improve both aspects. The methods used in this study include observation, literature review, and data analysis from various relevant sources. The development model used follows the Borg and Gall model (2007: 589), which has been revised by Sugiyono (2008) with seven stages, namely: identification of potential and problems, data collection, product design, design validation, design revision, product trials, and product revision. The results of this study produce a product, namely a development module that is expected to make a significant contribution to improving critical thinking skills through training. This module aims specifically to help individuals identify bias, distinguish between fact and opinion, and avoid misinformation.